2017
DOI: 10.1016/j.tiv.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide anion generation and oxidative stress in methylmercury-induced endothelial toxicity in vitro

Abstract: Emerging evidence has pointed to mercury exposure as a risk factor for hypertension, atherosclerosis, myocardial infarction and coronary heart disease. However, the underlying mechanisms are not well understood. This study investigated potential toxic effects of low concentrations of methylmercury (MeHg) in cultured bovine aortic endothelial cells (BAECs) and the possible involvement of reactive species, particularly superoxide anion, in mediating such toxicity. MeHg treatment increased the oxidation of 2',7'-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Oxidative stress has been suggested as a fundamental component of Hg‐induced testicular dysfunction (Venkatesan & Sadiq, 2017). Hg disturbs mitochondrial function and enhances the production of free radicals, including superoxide anions and peroxide radicals, which further trigger membrane LPO (Ghizoni et al, 2017). NO is a biological molecule that regulates blood pressure, neurotransmission, and immune response (Pierini & Bryan, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been suggested as a fundamental component of Hg‐induced testicular dysfunction (Venkatesan & Sadiq, 2017). Hg disturbs mitochondrial function and enhances the production of free radicals, including superoxide anions and peroxide radicals, which further trigger membrane LPO (Ghizoni et al, 2017). NO is a biological molecule that regulates blood pressure, neurotransmission, and immune response (Pierini & Bryan, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Calpain belongs to families of cysteine proteases and plays essential roles in the regulation and execution of necrotic cell death 45 . In addition to Bcl-2, Fas, and calpain, reactive oxygen species (ROS) such as hydrogen peroxide and superoxide have been shown to induce both apoptotic and necrotic forms of cell death 46 . A study by Ghizoni et al 46 aimed to determine the effects of MeHg exposure on superoxide generation and cellular glutathione (GSH) and toxicity in cultured bovine aortic endothelial cells (BAECs).…”
Section: Mercury-induced Apoptotic and Necrotic Cell Death Apoptosismentioning
confidence: 99%
“…In addition to Bcl-2, Fas, and calpain, reactive oxygen species (ROS) such as hydrogen peroxide and superoxide have been shown to induce both apoptotic and necrotic forms of cell death 46 . A study by Ghizoni et al 46 aimed to determine the effects of MeHg exposure on superoxide generation and cellular glutathione (GSH) and toxicity in cultured bovine aortic endothelial cells (BAECs). Results showed that exposure of 1 µM MeHg for 6 h significantly increased superoxide production and decreased levels of intracellular GSH 46 .…”
Section: Mercury-induced Apoptotic and Necrotic Cell Death Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…The increased formation of reactive oxygen species (ROS) is generally agreed to be one of the key mechanisms responsible for Hg-induced toxicity [ 26 28 ]. Mercury is endowed with high affinity for sulfhydryl groups, and it is therefore able to react with low-molecular-weight thiols, including glutathione (GSH) [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%